Do Respiratory Maneuvers Affect The Hepatic Vein Waveforms And Maximum Velocity? - Muhammad Salman Rafique, Sana Kundi, Ahmad Ziauddin, Tahir Malik, Asma Maqsood, Kayenat Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the effect of respiratory maneuvers on hepatic vein waveforms and flow velocity in patients without liver or cardiac disease. Methods: This prospective cross-sectional study was conducted in the Radiology Department of Pakistan Kidney and Liver Institute and Research Center, Lahore (PKLI & RC) after approval from Institutional Review Board (IRB). The sample size of 70 patients was selected using the WHO sample size calculator, after applying the inclusion and exclusion criteria. Doppler waveforms and maximum velocities (Vmax) of the middle hepatic vein were recorded during normal respiration, after quiet expiration, and following breath-hold after deep inspiration. The waveforms were classified as triphasic, biphasic, or monophasic. Results: The maximum velocities (Vmax) during normal respiration, after quiet expiration, and following deep inspiration were 26.67±9.41, 24.08±6.77 and 19.31±.61 respectively. During normal breathing, the middle hepatic vein waveforms were triphasic, biphasic and monophasic in 80%, 6%, and 14% of the patients respectively. After quiet expiration, these percentages were 82%, 4% & 14% respectively and following breath-hold after deep inspiration, these percentages were 41%, 14% and 45%, respectively (p<0.05). Conclusion: The hepatic venous velocities were lower after deep inspiration. Their waveforms showed significant change from triphasic pattern to monophasic pattern following deep inspiration. Therefore, the respiratory variations must be considered during hepatic vein Doppler ultrasound assessment.